Effect of Coenzyme Q10 Supplementation on Markers of Oxidative Stress in Streptozotocin Induced Diabetic Rats - Mona Anwar,Mehrevan Abd El-Moniem,Hoda A Megahed,Safinaz E EL-Toukhy,Nadia A Mohammed,Eman R Youness (Journal of Applied Pharmaceutical Science, 2014)
Increasing evidences link free radicals and oxidative stress to the pathogenesis of diabetes and related complications. The aim of this study was to investigate the effects of exogenous coenzyme Q10 supplementation on streptozotocin induced experimental diabetes in rats. Experimental diabetes was induced by single subcutaneous injection of streptozotocin ( 50 mg/kg/ body weight) . Forty male albino rats were used in this study, they were divided into 4 groups: control group, coenzyme Q10 treated group, diabetic group and coenzyme Q10 treated diabetic group. At the end of the experiment (8 weeks) urine samples were collected, rats were sacrificed and blood samples were collected for biochemical analysis. Significant high levels of blood sugar, glycated Hb, total cholesterol, triglyceride, LDL cholesterol, advanced oxidative protein products , 8-hydroxy-2-deoxyguanosine and percent of DNA damage as well as significant low levels of nitric oxide and HDL cholesterol were observed in diabetic group. Significant low levels of blood sugar, glycated Hb, cholesterol, triglyceride, LDL cholesterol, advanced oxidative protein products, 8-hydroxy-2-deoxyguanosine and percent of DNA damage as well as significant high levels of nitric oxide and HDL cholesterol were observed in coenzyme Q10 treated diabetic group. The data confirmed the property of coenzyme Q10 as an antioxidant that ameliorates oxidative stress and that it may be used as an additional therapeutic agent for prophylaxis and slowing down the progression diabetic complications.
Keywords: Oxidative stress, coenzyme Q10, streptozotocin, diabetes.